The Role of Vitamin D Sufficiency in the Formation of Benign Diseases of the Mammary Glands - Inoyatova Nodira Miranvarovna; Asatova Munira Miryusupovna (Researchparks Publishing, 2022)
Benign diseases of the mammary glands, being a